A paralog-specific role of COPI vesicles in the neuronal differentiation of mouse pluripotent cells - Goyal, Manu Jain; Zhao, Xiyan; Bozhinova, Mariya; Andrade-López, Karla; Heus, Cecilia de; Schulze-Dramac, Sandra; Müller-McNicoll, Michaela; Klumperman, Judith; Béthune, Julien (Life science alliance, 2020)
Coat protein complex I (COPI)-coated vesicles mediate membrane trafficking between Golgi cisternae as well as retrieval of proteins from the Golgi to the endoplasmic reticulum. There are several flavors of the COPI coat defined by paralogous subunits of the protein complex coatomer. However, whether paralogous COPI proteins have specific functions is currently unknown. Here, we show that the paralogous coatomer subunits γ1-COP and γ2-COP are differentially expressed during the neuronal differentiation of mouse pluripotent cells. Moreover, through a combination of genome editing experiments, we demonstrate that whereas γ-COP paralogs are largely functionally redundant, γ1-COP specifically promotes neurite outgrowth. Our work stresses a role of the COPI pathway in neuronal polarization and provides evidence for distinct functions for coatomer paralogous subunits in this process.
Gesehen am 09.11.2020